2013
DOI: 10.1039/c3ta11222e
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures and thermoelectric properties of layered BiCuOCh oxychalcogenides (Ch = S, Se and Te): first-principles calculations

Abstract: The p-type BiCuOCh (Ch ¼ S, Se and Te) compounds exhibit very low lattice thermal conductivities and moderate power factors in the medium temperature range, resulting in high thermoelectric figures of merit. In this paper, we investigated their electronic structures using density functional theory, and discovered that a mixture of heavy and light bands near the valence band maximum is beneficial for good thermoelectric performance, and the Cu 3d-Ch np antibonding state near the valence band edge determines the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
103
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 43 publications
14
103
0
Order By: Relevance
“…Moreover, the effect of SOC also changes the location of valence band maximum (VBM) from that between the M and Γ points to the Z point, which is different from previous theoretical predictions [15,29,30]. Similar picture can be found in Fig.…”
Section: B Band Structuresupporting
confidence: 30%
See 1 more Smart Citation
“…Moreover, the effect of SOC also changes the location of valence band maximum (VBM) from that between the M and Γ points to the Z point, which is different from previous theoretical predictions [15,29,30]. Similar picture can be found in Fig.…”
Section: B Band Structuresupporting
confidence: 30%
“…Apart from the intrinsic phonon-phonon interactions, the grain boundary and defect were also believed to be important 3 scattering mechanisms [6,9,10,14]. In the theoretical aspect, the electronic band structure of BiCuSeO was studied by performing first-principles calculations [15], which suggests that a mixture of heavy and light bands near the valence band edge can lead to a relatively higher Seebeck coefficient and a reasonable electrical conductivity. A comparative study [16] of BiCuSeO and its isostructural analog LaCuSeO indicates that Bi atom with higher atomic mass can produce lower phonon frequencies, smaller sound velocities, and a higher average mode Gruneisen parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the related oxychalcogenides [BiO][CuQ] (Q¼ S, Se, Te), which consist of [Bi 2 O 2 ] 2 þ layers alternating with [Cu 2 Q 2 ] 2 À layers [17], have been identified as promising p-type thermoelectric materials. In this system, it has been shown that the substitution of Se by Te leads to an increase in electrical conductivity [18,19], together with a reduction in the thermal conductivity ( $ 0.97 W m À 1 K À 1 for BiOCuSe [20] and 0.68 W m À 1 K À 1 for BiOCuTe [21] at 373 K). Consequently, the figure of merit of the oxytelluride (ZT¼ 0.42 at 373 K) is significantly higher than that of the oxyselenide (ZT ¼0.15 at 373 K) [20,21].…”
Section: Introductionmentioning
confidence: 98%
“…The low electrical conductivity caused by Ag-doping was further compensated by In-doping at Sn site, yielding the maximum zT = 1.42 in Cu 1. 85 Ag 0.15 Sn 0.9 In 0.1 Se 3 at 823 K. For Cu 2 GeSe 3 , the electrical conductivity is lower and the Seebeck coefficient is higher due to the large electronegativity of Ge. zT of~0.5 at 750 K were obtained in Ga-doped Cu 2 GeSe 3 samples [144].…”
Section: Distorted Diamond-like Chalcogenidesmentioning
confidence: 99%
“…Sn orbitals contribute little to the occupied states while predominantly affect the conductive band. The Cu-X conduction network has also been proposed in BiCuSeO [85], Cu 3 SbSe 4 [86], Cu 2 CdZnSe 4 [28], etc.…”
Section: Structural Retainer and Electrical Transportmentioning
confidence: 99%